The Roles of the Ubon Ratchathani Provincial Administrative Organization in the Management of Cultural Tourism: A Case Study of Pha Taem National Park, Ubon Ratchathani Province - Warpop, Jiraporn; Navakul, Suphanee (Journal of Chandrakasemsarn, 2022)
The objectives of this research study were to: 1) study the role of the Ubon Ratchathani Provincial Administrative Organization in the management of cultural tourism: a case study of Pha Taem National Park, Ubon Ratchathani Province; 2) study the problems and obstacles in the management of cultural tourism; and 3) determine the guidelines for the development of the role of the Ubon Ratchathani Provincial Administrative Organization in the management of cultural tourism. The study was conducted as a mixed-method. The quantitative research part employed questionnaire as a tool to collect data from 400 samples. The results were analyzed by using statistics of mean, standard deviation and Multiple Regression Analysis. In the qualitative research was conducted with 9 key informants using an in-depth interview. The Results reveal that of: 1) The analysis of the role of the Ubon Ratchathani Provincial Administrative Organization in the management of cultural tourism was found to be at “high level” ( = 4.15, SD = 0.62) following the role of tourist attraction aspect that it was at “highest level” ( = 4.27, SD = 0.61), as well as the role of facilities ( = 4.15, SD = 0.71); role of travel products ( = 4.12, SD = 0.70) and role of service were also found at “high level” ( = 4.06, SD = 0.71). 2)The relationship between management factors and the role of the Ubon Ratchathani Provincial Administrative Organization in the management of cultural tourism, market and manpower was found to be a positive correlation that affected the role of the Ubon Ratchathani Provincial Administrative Organization in the management of cultural tourism with statistically significant at the 0.05 level. Furthermore, 3) The guidelines for the development of the role of the Ubon Ratchathani PAO, would recommend that coordination among public sector, the private sector, as well as local people to promote and develop tourism be made possible. In addition, personnel should have more foreign language skills, in order to promote strategies for cooperation with neighboring provinces and organize more marketing promotion activities.